Kinetic and computational analysis of the reversible inhibition of porcine pancreatic elastase: a structural and mechanistic approach. (3rd November 2016) - Stergiou, Panagiota-Yiolanda; Foukis, Athanasios; Gkini, Olga A.; Bieth, Joseph G.; Papamichael, Emmanuel M.
Abstract: Structural and mechanistic insights were revealed for the reversible inhibition of Porcine Pancreatic Elastase (PPE); the kinetics of uninhibited and inhibited hydrolysis of substrate Suc-AAA-pNA was analyzed thoroughly. Additionally, the interactions between PPE and its inhibitor were studied by computational techniques. The uninhibited hydrolysis of Suc-AAA-pNA by PPE proceeds through a virtual transition state, involving an inferior physical and another dominating chemical step, where two stabilized reactant states precede the predominant acyl-enzyme. Different kinds of bonding with the PPE-backbone residues, including those of the catalytic triad, were found during the MD simulation of 5 ns, as key interactions favoring a higher stabilization of the best ranked complex PPE-CF3 C(O)-KA-NHPh-p-CF3 . The proton inventories of the inhibited hydrolysis of Suc-AAA-pNA by PPE, were ruled out the existence of any virtual transition state and thus they argue for a different mode of catalysis involving a structurally disturbed PPE molecule. Thereafter, a novel inhibition mechanism was suggested.